Comparison of performances of infliximab biosimilars CT-P13 versus SB2 in the treatment of inflammatory bowel diseases: a real-life multicenter, observational study in Italy. (1st February 2022) - Tursi, Antonio; Mocci, Giammarco; Allegretta, Leonardo; Aragona, Giovanni; Bianco, Maria Antonia; Colucci, Raffaele; Cuomo, Antonio; Della Valle, Nicola; Ferronato, Antonio; Forti, Giacomo; Gaiani, Federica; Graziani, Maria Giovanna; et al.
ABSTRACT: Background: To compare the performances of Infliximab (IFX) biosimilar CT-P13 and SB2 in the treatment of Inflammatory Bowel Diseases (IBD) outpatients in Italy. Research Design and Methods: Three hundred and eighty IBD outpatients were retrospectively evaluated. The primary endpoint was to compare the two IFX biosimilars in terms of reaching and maintenance of remission at any timepoint. Results: 197 patients with Ulcerative Colitis (UC) and 183 patients with Crohn's Disease (CD) treated with CT-P13 or SB2 and having a median (IQR) follow-up of 12 (6–36) months were compared: 230 (60.5%) were naïve to anti-TNFα, 20 (5.26%) were switched from IFX originator or from IFX CT-P13 to IFX SB2. Clinical remission was achieved in 133 (67.5%) UC patients and in 164 (89.6%) CD patients (p < 0.000), with no differences between CT-P13 and SB2 in the rate of remission in UC (p = 0.667) and CD (p = 0.286). Clinical response, steroid-free remission, rate of surgery, mucosal healing (MH) in UC, switching from IFX originator or from other biosimilar, and safety were similar. Higher MH rate was obtained in CD patients treated with CT-P13 (p = 0.004). Conclusion: This first comparative study found that both IFX biosimilars CT-P13 and SB2 are effective and safe in managing IBD outpatients.